Minorities and Small Numbers from Molecules to Organisms in Biology Toward a New Understanding of Biological Phenomena (Springer Singapore, 2018)
This book provides an accessible introduction to an exciting new field of life science in which the focus is on small numbers of molecules and minorities within cell populations and their significance for the understanding of biological phenomena. Numbers, or quantitative data, are attracting more attention in cell biology following, for example, determination of the absolute copy number of each protein species in each bacterial cell and the recognition of leader cells that drive collective cell migration. Within this context, the authors present recent advances in experimental techniques, biological findings, and theories. A variety of cutting-edge topics and issues are addressed, with explanation of the ways in which recent developments in the field cast light on seemingly straightforward but difficult-to-answer questions. Readers will learn that we are on the verge of a paradigm shift as the importance of cooperation among groups of molecules in live cells is acknowledged. The book is designed to be enjoyable to read and easy to understand. It will be of interest for a wide range of readers, including young researchers and undergraduate/high school students.